2004
DOI: 10.1242/jcs.01385
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin associates with N-cadherin adhesions and mediates intercellular adhesion strengthening in fibroblasts

Abstract: The regulation of N-cadherin-mediated intercellular adhesion strength in fibroblasts is poorly characterized; this is due, in part, to a lack of available quantitative models. We used a recombinant N-cadherin chimeric protein and a Rat 2 fibroblast, donor-acceptor cell model, to study the importance of cortical actin filaments and cortactin in the strengthening of N-cadherin adhesions. In wash-off assays, cytochalasin D (1 μM) reduced intercellular adhesion by threefold, confirming the importance of cortical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 69 publications
8
64
1
Order By: Relevance
“…Second, cadherin recruitment of PI 3-kinase was also abolished in SYF-null cells lacking the ubiquitous Src family members, and recruitment was restored by expression of c-Src alone. This positive contribution of Src to cadherin signaling is consistent with the earlier demonstrations that Fyn was necessary for the efficient assembly of cell-cell junctions in keratinocytes (33), and Src inhibitors reduced N-cadherin adhesiveness (37). Furthermore, in other experimental systems, Src is often required for PI 3-kinase to interact with growth factor and cytokine receptors (6,7).…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, cadherin recruitment of PI 3-kinase was also abolished in SYF-null cells lacking the ubiquitous Src family members, and recruitment was restored by expression of c-Src alone. This positive contribution of Src to cadherin signaling is consistent with the earlier demonstrations that Fyn was necessary for the efficient assembly of cell-cell junctions in keratinocytes (33), and Src inhibitors reduced N-cadherin adhesiveness (37). Furthermore, in other experimental systems, Src is often required for PI 3-kinase to interact with growth factor and cytokine receptors (6,7).…”
Section: Figsupporting
confidence: 89%
“…Several earlier reports also suggested that tyrosine kinases might contribute positively to cadherin function (37). Notably, Calautti et al (33) reported that tyrosine kinase signaling was necessary for differentiating keratinocytes to assemble cadherin-based cell-cell contacts.…”
Section: Figmentioning
confidence: 97%
“…Functionally, knockdown of cortactin ablated the regulation of Kv1.5 channel activity by N-cadherin in the oocyte expression system, strongly supporting the idea of an N-cadherin-cortical actin-cortactin-Kv1.5 axis. In nonmyocytes, cortactin has been shown to interact with the cadherin-catenin complex (51,52); however, we did not detect N-cadherin-cortactin association by co-immunoprecipitation in heart tissue. This result suggests that N-cadherin-cortactin association is cell type-dependent.…”
Section: Potential Roles Of Cortactin-actin Cytoskeleton In Regulatingcontrasting
confidence: 58%
“…Indeed, ␤-catenin is well known to physically link cadherin receptors to actin filaments through binding to ␣-catenin . Conversely, p120 catenin is known to modulate cadherin adhesiveness (Ozawa and Kemler, 1998;Yap et al, 1998;Thoumine et al, 2006) and was reported to bind cortactin (El Sayegh et al, 2004), providing a potential parallel pathway to connect N-cadherin to the actin network. However, the effects of Ncad⌬␤cat and NcadAAA were not completely specific of the Ncad-Fc substrate, as these mutants also reduced neurite extension on laminin-coated glass.…”
Section: Discussionmentioning
confidence: 99%